Cultivation and Genomics Prove Long-Term Colonization of Donor’s Bifidobacteria in Recurrent Clostridioides difficile Patients Treated With Fecal Microbiota Transplantation - Jouhten, Hanne; Ronkainen, Aki; Aakko, Juhani; Salminen, Seppo; Mattila, Eero; Arkkila, Perttu; Satokari, Reetta (Frontiers in Microbiology, 2020)
Fecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridioides difficile infection (rCDI) and it’s also considered for treating other indications. Metagenomic studies have indicated that commensal donor bacteria may colonize FMT recipients, but cultivation has not been employed to verify strain-level colonization. We combined molecular profiling of Bifidobacterium populations with cultivation, molecular typing, and whole genome sequencing (WGS) to isolate and identify strains that were transferred from donors to recipients. Several Bifidobacterium strains from two donors were recovered from thirteen recipients during the one-year follow-up period after FMT. The strain identities were confirmed by WGS and comparative genomics. Our results show that specific donor-derived bifidobacteria can colonize rCDI patients for at least one year, and thus FMT may have long-term consequences for the recipient´s microbiota and health. Conceptually, we demonstrate that FMT trials combined with microbial profiling can be used as a platform for discovering and isolating commensal strains with proven colonization capacity for potential therapeutic use.